A coupled analytical-numerical approach for optimal sizing of power inductors. Issue 5 (26th August 2014) - Makni, Zaatar; Demersseman, Richard
Abstract : Purpose: – The purpose of this paper is to present an optimal sizing methodology. It is applied to a foil-coil powder core power inductor used in new generation inverters designed for hybrid and full-electric vehicles. The methodology includes a preliminary analytical calculation and a numerical optimization aimed at minimizing the component size. Design/methodology/approach: – Unlike bulk magnetic alloys or ferrites, the magnetic non-linearity of powder materials cannot be neglected in the analytical calculation. This non-linearity requires the use of an iterative calculation to search the set of parameters for which the target inductance value and the minimum volume are simultaneously reached. The numerical optimization process is based on 2D Finite Element (FE) analysis carried out with FEMM software tool and a simplex-type algorithm run in Scilab software. These two freewares are coupled using the scifemm.sci script which is included in the FEMM distribution. Findings: – The association of analytical and FE approaches provides a relevant and quick sizing methodology. It was successfully applied to size a new power inductor. Originality/value: – The strong non-linearity of the powder material is correctly taken into account in the analytical model thanks to an iterative calculation process. Thus, the preliminary analytical solution is quite relevant. Consequently, a local FE-based optimization is enough to find the optimal solution close by the analytical one. No global optimization is required. A local optimum is sufficient.